Effect of Staining and Aging on Translucency Parameter of CAD-CAM Materials - Rubens Nisie Tango; Ana Todorović; Dejan Stamenković; Duygu Narin Karasan; Irena Sailer; Rade Dušan Paravina (University of Zagreb. School of Dental Medicine, 2021)
Objectives: To evaluate different intervals of exposure to staining solutions and artificial aging on translucency parameter (TP 00) of CAD-CAM materials. Material and Methods: One millimeter thick square-shaped specimens (N = 288) were cut from Cerasmart (CS), IPS e.max (IE), Lava Ultimate (LU), Shofu HC (SH), Vita Enamic (VE), and Vita Suprinity (VS) and were divided into laboratory and chairside polishing. Reflection wavelength spectra, CIE D65 standard illuminant, 2 ° standard observer, SCI, UV included, SAV aperture, 6 mm diameter, were recorded at 10 nm sensitivity against white and black calibration tiles using a benchtop spectrophotometer. Subsequently, they were converted into CIEDE 2000 TP 00. After baseline measurements (T0), the specimens were divided as follows (n = 8): staining in coffee (C) and wine (W), for 60 (T1) and 120 hours (T2), and accelerated artificial aging (A). Artificial aging (ISO 4892-2 standard) was performed in two cycles of 150 KJ/m 2, for T1 and T2, respectively. TP measurements were repeated at T1 and T2. Data of TP 00 retention were submitted to analysis of variance and Fisher's PLSD multiple comparison test (α=0.05). Results: Fisher's PLSD critical differences among materials, time intervals and staining/aging were 0.16, 0.11 and 0.11, respectively. SH showed the highest TP 00 followed by LU > CS > IE = VS > VE. For all time intervals, the lowest TP 00 retention was observed with C. W, and A presented similar values. Conclusions: Translucency Parameter was material, time and staining/aging-dependent material. In majority of cases, it decreased upon staining/aging.